2013
DOI: 10.1111/1574-6976.12022
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the metabolic activities of human-associated microbial communities across multiple ecological scales

Abstract: Humans are home to complex microbial communities, whose aggregate genomes and their encoded metabolic activities are referred to as the human microbiome. Recently, researchers have begun to appreciate that different human body habitats and the activities of their resident microorganisms can be better understood in ecological terms, as a range of spatial scales encompassing single cells, guilds of microorganisms responsive to a similar substrate, microbial communities, body habitats, and host populations. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 168 publications
(235 reference statements)
0
21
0
Order By: Relevance
“…The strongest negative ratios were observed in Streptococcus , Veillonella , Enterococcus and Blautia whereas the positive ratios observed for Faecalibacterium, Flavonifractor and Oscillibater suggested high biological activity. Thus, our metaproteomics data revealed that the gut microbiota harbours a distinctive subset of biologically active microorganisms as consistently shown in other reports (McNulty et al ., ; Ferrer et al ., ; Maurice et al ., ; Maurice and Turnbaugh, ; Perez‐Cobas et al ., ). While we cannot exclude analytical biases in DNA and protein extraction methods, these discordances suggest that using bacterial taxa as input information to build predictive theoretical models of microbial activity and contribution to community functioning in human gut microbial ecosystems may be highly misleading.…”
Section: Resultsmentioning
confidence: 99%
“…The strongest negative ratios were observed in Streptococcus , Veillonella , Enterococcus and Blautia whereas the positive ratios observed for Faecalibacterium, Flavonifractor and Oscillibater suggested high biological activity. Thus, our metaproteomics data revealed that the gut microbiota harbours a distinctive subset of biologically active microorganisms as consistently shown in other reports (McNulty et al ., ; Ferrer et al ., ; Maurice et al ., ; Maurice and Turnbaugh, ; Perez‐Cobas et al ., ). While we cannot exclude analytical biases in DNA and protein extraction methods, these discordances suggest that using bacterial taxa as input information to build predictive theoretical models of microbial activity and contribution to community functioning in human gut microbial ecosystems may be highly misleading.…”
Section: Resultsmentioning
confidence: 99%
“…Characterization and quantification of individual microbial cells can be achieved using flow cytometry with tandem mass spectrometry to measure metabolic activity 106 . This single-cell strategy enables the analysis of cell-to-cell functional variation and the discovery of novel regulatory mechanisms.…”
Section: Figurementioning
confidence: 99%
“…Recent advances in the culture-independent interrogation of microbial community structure 1, 2 and function 24 , including advances in sequencing technologies and the development of bioinformatic tools, have spawned a veritable “ microbiome renaissance”. Due to these advances, the microbiota is now often referred to as the “forgotten organ” due to our understanding and appreciation of its contributions to host physiology, metabolism, and disease 5 .…”
mentioning
confidence: 99%